2018
DOI: 10.1039/c8ra02687d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of propellanes containing a bicyclo[2.2.2]octene unitviathe Diels–Alder reaction and ring-closing metathesis as key steps

Abstract: The synthesis of propellanes containing bicyclo[2.2.2]octene via olefin metathesis approach is less explored.Herein, we describe a simple and convenient method to synthesize propellane derivatives containing a bicyclo[2.2.2]octene unit which are structurally similar to 11b-HSD1 inhibitors by sequential usage of the Diels-Alder reaction, C-allylation and ring-closing metathesis (RCM) as the key steps. Additionally, we expanded this approach to an endo-tricyclo[4.2.2.0 2,5 ]decene derivative which is a useful mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…However, it was found that the pure trans-isomers 6aA, 6eA and 6pA are able to form tricyclic systems of cyclopenta[b]furo[2,3-c]pyrrole 7 in the RRM reaction (the last column of Tables 2 and 4). Moreover, in contrast to the communications [9][10][11]17,19,21,22], in our case, the ring-rearrangement metathesis does not require the supporting application of ethylene that facilitates practical synthesis. To achieve the maximum yield of the target tricycles 7, the metathesis reaction was optimized in terms of solvent, temperature, duration and amount of catalyst.…”
Section: Scheme 6 Results Of Metathesis Of Cis-isomers 6bmentioning
confidence: 88%
See 3 more Smart Citations
“…However, it was found that the pure trans-isomers 6aA, 6eA and 6pA are able to form tricyclic systems of cyclopenta[b]furo[2,3-c]pyrrole 7 in the RRM reaction (the last column of Tables 2 and 4). Moreover, in contrast to the communications [9][10][11]17,19,21,22], in our case, the ring-rearrangement metathesis does not require the supporting application of ethylene that facilitates practical synthesis. To achieve the maximum yield of the target tricycles 7, the metathesis reaction was optimized in terms of solvent, temperature, duration and amount of catalyst.…”
Section: Scheme 6 Results Of Metathesis Of Cis-isomers 6bmentioning
confidence: 88%
“…It worth mentioning here that by revising the ethylene-supported transformations of the similar substrates [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], the question of the sequence of metathesis stages arose. In theory, two paths exist for the rearrangement of 6 to 7 in an ethylene atmosphere: ROM/RCM, or vice versa, RCM/ROM successions [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also demonstrated an elegant strategy for the synthesis of propellanes 194 , 196 , and 199 from commercially available starting materials . To this end, the cycloaddition reaction of cyclooctatetraene 187 and maleic anhydride 188 gave the known cycloadduct 189 , which on condensation with aniline gave the N ‐phenyl derivative 191 .…”
Section: Propellanesmentioning
confidence: 99%